2004
DOI: 10.1111/j.1651-2227.2004.tb03025.x
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal microflora in breastfed colicky and non‐colicky infants

Abstract: Our study indicates that colicky infants have different patterns of gut microflora. Further studies are required to understand whether gut microflora is the primary cause of colics or its consequence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
86
1
5

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 130 publications
(96 citation statements)
references
References 26 publications
4
86
1
5
Order By: Relevance
“…Our data are in line with the literature that has reported that the bacterial composition of faecal microflora is different in infants with and without colic (3)(4)(5)(6)(7)(8) and add new information about formula-fed infants. Intestinal microbiota can be investigated either by microbial quantification and by characterising some strains or by studying the metabolites produced, in this case ammonia, that can be considered as a marker for proteolytic fermentation by Enterobacteriaceae (13,23).…”
Section: Limitationssupporting
confidence: 81%
See 1 more Smart Citation
“…Our data are in line with the literature that has reported that the bacterial composition of faecal microflora is different in infants with and without colic (3)(4)(5)(6)(7)(8) and add new information about formula-fed infants. Intestinal microbiota can be investigated either by microbial quantification and by characterising some strains or by studying the metabolites produced, in this case ammonia, that can be considered as a marker for proteolytic fermentation by Enterobacteriaceae (13,23).…”
Section: Limitationssupporting
confidence: 81%
“…A peculiar gut microbial composition, such as a lower lactobacilli concentration in the first months of life, may favour the development of infantile colic (3). Furthermore, colicky infants present with higher counts of anaerobic Gram-negative bacteria and lower counts of intestinal lactobacilli than infants without colic (4,5). Additional proof of the link between the gut microbiota and infantile colic derives from a study in which gas-forming coliforms were prevalent in infants with colic but not in infants without colic (6).…”
Section: Introductionmentioning
confidence: 95%
“…Moreover, not only the steric distribution of fatty acids and carbohydrates lead to more physiological metabolism of nutrients and improve gut omeostasis but also the OS content seems to have a human milk-similar effect in growth Randomized controlled study for infantile colic F Savino et al promotion of beneficial intestinal flora (Lucas et al, 1997;Boehm et al, 2004;Knol et al, 2005). Growing evidence underlines that common gut disorders in infancy (including infantile colic, meterorism, flatulence, food intolerance and allergy) can also be mediated by gut flora (Lehtonen et al, 1994;Lindberg, 1999;Haller and Jobin, 2004;Savino et al, 2004Savino et al, , 2005. Breast-fed infants have been detected for a characteristic gut microflora (Walker and Duffy, 1998;Fanaro et al, 2003;Rinne et al, 2005) as well as colicky compared to non-colicky infants (Lehtonen et al, 1994;Savino et al, 2004Savino et al, , 2005.…”
Section: Molecular Weight Distribution (Kda ¼ Kilodalton)mentioning
confidence: 99%
“…Growing evidence underlines that common gut disorders in infancy (including infantile colic, meterorism, flatulence, food intolerance and allergy) can also be mediated by gut flora (Lehtonen et al, 1994;Lindberg, 1999;Haller and Jobin, 2004;Savino et al, 2004Savino et al, , 2005. Breast-fed infants have been detected for a characteristic gut microflora (Walker and Duffy, 1998;Fanaro et al, 2003;Rinne et al, 2005) as well as colicky compared to non-colicky infants (Lehtonen et al, 1994;Savino et al, 2004Savino et al, , 2005. Bifidobacteria and Lactobacillus seem to be predominant in breast-fed and notcolicky infants, whereas Gram-negative anaerobic bacteria seem to be predominant in the formula-fed and colicky ones.…”
Section: Molecular Weight Distribution (Kda ¼ Kilodalton)mentioning
confidence: 99%
See 1 more Smart Citation